Health Literacy: Improving Health, Health Systems, and Health Policy Around the World: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
The roots of health literacy can be traced back to the national literacy movement in India under Gandhi and to aid groups working in Africa to promote education and health. The term health literacy was first used in 1974 and described as "health education meeting minimal standards for all school grade levels". From that first use the definition of health literacy evolved during the next 30 years with official definitions promulgated by government agencies and large programs. Despite differences among these definitions, they all hold in common the idea that health literacy involves the need for people to understand information that helps them maintain good health. Although the United States produces a majority of the research on health literacy, Europe has strong multinational programs as well as research efforts, and health literacy experts in developing countries have created successful programs implemented on a community level. Given these distinct strengths of efforts worldwide, there are many opportunities for collaboration. International collaboration can harness the United States' research power, Europe's multilingual and multinational experience, and developing nations' community-based programs to create robust programs and research that reach people—not based on language or nationality but on need and value. A workshop on international health literacy efforts that feature presentations and discussion about health literacy interventions from various countries as well as other topics related to international health literacy was held as the basis for this report. Health Literacy: Improving Health, Health Systems, and Health Policy Around the World summarizes the findings and discussions at the workshop.
Keywords: Health and Medicine

Developing Health Literacy Skills in Children and Youth: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Young people develop health literacy skills in a variety of environments, facing critical thinking challenges about their health from school, home and family life, peers and social life, and online. To explore the development of health literacy skills in youth, the Roundtable on Health Literacy convened a workshop on November 19, 2019, in Washington, DC. Presenters at the workshop discussed factors relating to health literacy skills and ways to further develop those skills among youth from early childhood to young adulthood. This publication summarizes the presentation and discussion of the workshop.
Keywords: Health and Medicine

Health Literacy and Communication Strategies in Oncology: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Health literacy is a critical skill for engaging in healthy behaviors to reduce disease risk and improve health outcomes across the continuum of cancer care. However, estimates suggest that more than one-third of the U.S. adult population has low health literacy, and nearly half of all patients with cancer have difficulty understanding information about their disease or treatment. Low health literacy among patients with cancer is associated with poor health and treatment outcomes, including lower adherence to treatment, higher rates of missed appointments, and an increased risk of hospitalization. Low health literacy can also impede informed decision making, especially as cancer care becomes increasingly complex and as patients and their families take more active roles in treatment decisions. To examine opportunities to improve communication across the cancer care continuum, the National Cancer Policy Forum collaborated with the Roundtable on Health Literacy to host a workshop, Health Literacy and Communication Strategies in Oncology, July 15-16, 2019, in Washington, DC. Patients, patient advocates, clinicians, and researchers, representatives of health care organizations, academic medical centers, insurers, and federal agencies explored the challenges of achieving effective communication in cancer care. This publication summarizes the presentations and discussions of the workshop.
Keywords: Health and Medicine

Community-Based Health Literacy Interventions: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
In its landmark report, Health Literacy: A Prescription to End Confusion, the Institute of Medicine noted that there are 90 million adults in the United States with limited health literacy who cannot fully benefit from what the health and health care systems have to offer. Since the release of that report, health literacy has become a vibrant research field that has developed and disseminated a wide range of tools and practices that have helped organizations, ranging in size from large health care systems to individual health care providers and pharmacists, to engage in health literate discussions with and provide health literate materials for patients and family members. Improving the health literacy of organizations can be an important component of addressing the social determinants of health and achieving the triple aim of improving the patient experience, improving the health of populations, and reducing the cost of care. However, the focus on organizations does not address the larger issue of how to improve health literacy across the U.S. population.
Keywords: Health and Medicine

Building the Case for Health Literacy: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The field of health literacy has evolved from one focused on individuals to one that recognizes that health literacy is multidimensional. While communicating in a health literate manner is important for everyone, it is particularly important when communicating with those with limited health literacy who also experience more serious medication errors, higher rates of hospitalization and use of the emergency room, poor health outcomes, and increased mortality. Over the past decade, research has shown that health literacy interventions can significantly impact various areas including health care costs, outcomes, and health disparities.
Keywords: Health and Medicine

Relevance of Health Literacy to Precision Medicine: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
On January 20, 2015, President Obama announced the Precision Medicine Initiative (PMI) in his State of the Union address. The PMI, by developing new approaches for detecting, measuring, and analyzing a wide range of biomedical information including molecular, genomic, cellular, clinical, behavioral, physiological, and environmental parameters, is intended to enable a new era of medicine in which researchers, providers, and patients work together to develop individualized care. Part of this effort included the creation of a national, large-scale research participant group, or cohort. The PMI Cohort Program is aimed at extending precision medicine to many diseases, including both rare and common diseases such as diabetes, heart disease, Alzheimer's disease, obesity, and mental illnesses such as depression, bipolar disorder, and schizophrenia, by building a national research cohort of 1 million or more U.S. participants.
Keywords: Health and Medicine

Informed Consent and Health Literacy: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
Informed consent - the process of communication between a patient or research subject and a physician or researcher that results in the explicit agreement to undergo a specific medical intervention - is an ethical concept based on the principle that all patients and research subjects should understand and agree to the potential consequences of the clinical care they receive. Regulations that govern the attainment of informed consent for treatment and research are crucial to ensuring that medical care and research are conducted in an ethical manner and with the utmost respect for individual preferences and dignity. These regulations, however, often require - or are perceived to require - that informed consent documents and related materials contain language that is beyond the comprehension level of most patients and study participants. To explore what actions can be taken to help close the gap between what is required in the informed consent process and communicating it in a health-literate and meaningful manner to individuals, the Institute of Medicine's Roundtable on Health Literacy convened a one-day public workshop featuring presentations and discussions that examine the implications of health literacy for informed consent for both research involving human subjects and treatment of patients. Topics covered in this workshop included an overview of the ethical imperative to gain informed consent from patients and research participants, a review of the current state and best practices for informed consent in research and treatment, the connection between poor informed consent processes and minority underrepresentation in research, new approaches to informed consent that reflect principles of health literacy, and the future of informed consent in the treatment and research settings. Informed Consent and Health Literacy is the summary of the presentations and discussion of the workshop.
Keywords: Health and Medicine

Health Literacy: Past, Present, and Future: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
In 2004, the Institute of Medicine released Health Literacy: A Prescription to End Confusion, a report on the then-underappreciated challenge of enabling patients to comprehend their condition and treatment, to make the best decisions for their care, and to take the right medications at the right time in the intended dose. That report documented the problems, origins, and consequences of the fact that tens of millions of U.S. adults are unable to read complex texts, including many health-related materials, and it proposed possible solutions to those problems. To commemorate the anniversary of the release of the 2004 health literacy report, the Institute of Medicine's Roundtable on Health Literacy convened a 1-day public workshop to assess the progress made in the field of health literacy over the past decade, the current state of the field, and the future of health literacy at the local, national, and international levels. Health Literacy: Past, Present, and Future summarizes the presentation and discussion of the workshop.
Keywords: Health and Medicine

Health Literacy and Older Adults: Reshaping the Landscape: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Adults age 65 and older make up the fastest-growing segment of the U.S. population. At the same time, the complexity of health care delivery continues to grow, creating challenges that are magnified for older adults, given that age is one of the highest correlates of low health literacy. This creates a shared obligation between health care and the health care team to use the principles, tools, and practices of health literacy so that patients and families of older adults can more easily navigate discussions related to chronic disease, polypharmacy, long-term care, palliative care, insurance complexities, the social determinants of health, and other factors that create challenges for older adults, particularly among underserved populations nationwide.
Keywords: Health and Medicine

Oral Health Literacy: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
The Institute of Medicine (IOM) Roundtable on Health Literacy focuses on bringing together leaders from the federal government, foundations, health plans, associations, and private companies to address challenges facing health literacy practice and research and to identify approaches to promote health literacy in both the public and private sectors. The roundtable serves to educate the public, press, and policy makers regarding the issues of health literacy, sponsoring workshops to discuss approaches to resolve health literacy challenges. It also builds partnerships to move the field of health literacy forward by translating research findings into practical strategies for implementation. The Roundtable held a workshop March 29, 2012, to explore the field of oral health literacy. The workshop was organized by an independent planning committee in accordance with the procedures of the National Academy of Sciences. The planning group was composed of Sharon Barrett, Benard P. Dreyer, Alice M. Horowitz, Clarence Pearson, and Rima Rudd. The role of the workshop planning committee was limited to planning the workshop. Unlike a consensus committee report, a workshop summary may not contain conclusions and recommendations, except as expressed by and attributed to individual presenters and participants. Therefore, the summary has been prepared by the workshop rapporteur as a factual summary of what occurred at the workshop.
Keywords: Health and Medicine

The Intersection of Behavioral Health, Mental Health, and Health Literacy: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
The field of health literacy has evolved from early efforts that focused on individuals to its current recognition that health literacy is a multidimensional team and system function. Health literacy includes system demands and complexities as well as individual skills and abilities. While communicating in a health-literate manner is truly important for everyone, it can be especially important for those with mental or behavioral health issues and for the systems and teams that interact with them and treat these individuals.
Keywords: Health and Medicine

Health Literacy and Consumer-Facing Technology: Workshop Summary - Institute of Medicine; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
The proliferation of consumer-facing technology and personal health information technology has grown steadily over the past decade, and has certainly exploded over the past several years. Many people have embraced smartphones and wearable health-monitoring devices to track their fitness and personal health information. Providers have made it easier for patients and caregivers to access health records and communicate through online patient portals. However, the large volume of health-related information that these devices can generate and input into a health record can also lead to an increased amount of confusion on the part of users and caregivers. The Institute of Medicine convened a workshop to explore health literate practices in health information technology and then provide and consider the ramifications of this rapidly growing field on the health literacy of users. Health Literacy and Consumer-Facing Technology summarizes the discussions and presentations from this workshop, highlighting the lessons presented, practical strategies, and the needs and opportunities for improving health literacy in consumer-facing technology.
Keywords: Health and Medicine

Integrating Oral and General Health Through Health Literacy Practices: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Oral health care and medical health care both seek to maintain and enhance human health and well-being. Yet, dentistry and primary care in the United States are largely separated and isolated from each other. Each has its own siloed systems for education, service delivery, financing, and policy oversight. The result has been duplication of effort, a cultural gap between the two professions, and lost opportunities for productive collaboration and better health.
Keywords: Health and Medicine

Integrating Health Literacy, Cultural Competence, and Language Access Services: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The aging and evolving racial and ethnic composition of the U.S. population has the United States in the midst of a profound demographic shift and health care organizations face many issues as they move to address and adapt to this change. In their drive to adequately serve increasingly diverse communities, health care organizations are searching for approaches that will enable them to provide information and service to all persons, regardless of age, race, cultural background, or language skills, in a manner that facilitates understanding and use of that information to make appropriate health decisions.
Keywords: Health and Medicine

Implications of Health Literacy for Public Health: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Health literacy is the degree to which individuals can obtain, process, and understand the basic health information and services they need to make appropriate health decisions. Nearly half of all American adults - 90 million people - have inadequate health literacy to navigate the health care system. Implications of Health Literacy for Public Health is the summary of a workshop convened by the Institute of Medicine Roundtable on Health Literacy in November 2013 that focused on the implications of health literacy for the mission and essential services of public health. The workshop featured the presentation of a commissioned paper on health literacy activities under way in public health organizations. Other presentations examined the implications of health literacy for the mission and essential services of public health, for example, community health and safety, disease prevention, disaster management, or health communication. This report includes the commissioned paper and summaries of the workshop presentations.
Keywords: Health and Medicine

Organizational Change to Improve Health Literacy: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
Organizational Change to Improve Health Literacy is the summary of a workshop convened in April 2013 by the Institute of Medicine Board on Population Health and Public Health Practice Roundtable on Health Literacy. As a follow up to the 2012 discussion paper Ten Attributes of a Health Literate Health Care Organization, participants met to examine what is known about implementation of the attributes of a health literate health care organization and to create a network of health literacy implementers who can share information about health literacy innovations and problem solving. This report discusses implementation approaches and shares tools that could be used in implementing specific literacy strategies. Although health literacy is commonly defined as an individual trait, there is a growing appreciation that health literacy does not depend on the skills of individuals alone. Health literacy is the product of the interaction between individuals' capacities and the health literacy-related demands and complexities of the health care system. System changes are needed to better align health care demands with the public's skills and abilities. Organizational Change to Improve Health Literacy focuses on changes that could be made to achieve this goal.
Keywords: Health and Medicine

Facilitating Health Communication with Immigrant, Refugee, and Migrant Populations Through the Use of Health Literacy and Community Engagement Strategies: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
The increasingly diverse ethnic composition of the United States population has created a profound and ongoing demographic shift, and public health and health care organizations face many challenges as they move to address and adapt to this change. To better understand how the public health and health care communities can meet the challenges of serving an increasingly diverse population, the Roundtable on Health Literacy conducted a public workshop on facilitating health communication with immigrant, refugee, and migrant populations through the use of health literate approaches. The goal of the workshop was to identify approaches that will enable organizations that serve these ethnically and culturally diverse populations in a manner that allows all members of these communities to obtain, process, and understand basic health information and the services needed to make appropriate health and personal decisions. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Health Insurance and Insights from Health Literacy: Helping Consumers Understand: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Since the passage of the Patient Protection and Affordable Care Act (ACA), health care reform has created major changes in the U.S. health care system. The ACA has brought millions of people into the system who had no previous access, and many of these newly enrolled individuals have had limited experience navigating the complex and complicated U.S. health system.
Keywords: Health and Medicine

Health Literacy and Palliative Care: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The Institute of Medicine Roundtable on Health Literacy convened a 1-day public workshop to explore the relationship between palliative care and health literacy, and the importance of health literate communication in providing high-quality delivery of palliative care. Health Literacy and Palliative Care summarizes the discussions that occurred throughout the workshop and highlights the key lessons presented, practical strategies, and the needs and opportunities for improving health literacy in the United States.
Keywords: Health and Medicine

Health Literacy and Numeracy: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
Although health literacy is commonly defined as an individual trait, it does not depend on the skills of individuals alone. Health literacy is the product of the interaction between individuals' capacities and the health literacy-related demands and complexities of the health care system. Specifically, the ability to understand, evaluate, and use numbers is important to making informed health care choices. Health Literacy and Numeracy is the summary of a workshop convened by The Institute of Medicine Roundtable on Health Literacy in July 2013 to discuss topics related to numeracy, including the effects of ill health on cognitive capacity, issues with communication of health information to the public, and communicating numeric information for decision making. This report includes a paper commissioned by the Roundtable, "Numeracy and the Affordable Care Act: Opportunities and Challenges," that discusses research findings about people's numeracy skill levels; the kinds of numeracy skills that are needed to select a health plan, choose treatments, and understand medication instructions; and how providers should communicate with those with low numeracy skills. The paper was featured in the workshop and served as the basis of discussion.
Keywords: Health and Medicine